ANALISIS KEMAMPUAN MEMBACA PERMULAAN KELAS 2 MI ATS TSAUROH - Natika Kamilah; Desty Endrawati Subroto; Muamalah, Muamalah; Dini Astuti (Sindoro: Cendikia Pendidikan, 2025)
This study aims to identify the initial reading difficulties experienced by grade 2 students of MI Ats Tsauroh, as well as the factors that influence and the solutions provided by teachers to overcome these difficulties. Based on observations and interviews with teachers and the principal, it was found that some students experienced difficulties in reading, such as difficulties in spelling, reading word order, reading diphthongs, and understanding the meaning of words. Factors that influence these difficulties include internal factors, such as students' attitudes and interests in learning, intelligence, and students' awareness of the importance of reading. Meanwhile, external factors include the family and school environment. To overcome these difficulties, teachers apply various solutions, such as counseling, increasing reading hours after KBM, and using learning methods such as the alphabet method, letter cards, spelling, and dictation. This study shows that with the right strategy, initial reading difficulties can be overcome, so that students' reading ability can improve.